A security community in Africa : a critical assessment of the African Union’s contribution towards the construction of a potential security community since 2002 - De Vos, Johannes Nicolaas (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2012.